2007
DOI: 10.1089/sur.2006.065
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Late Tracheostomy in Patients with Severe Traumatic Head Injury

Abstract: Early tracheostomy was beneficial, resulting in a shorter ICU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
15

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 27 publications
3
75
1
15
Order By: Relevance
“…49 A retrospective cohort study compared 27 TBI subjects who received early tracheostomy (Ͻ 7 d of intubation) versus 28 TBI subjects with late tracheostomy (Ͼ 7 d of intubation) and found that early tracheostomy was associated with decreased ICU stay, but had no effect on hospital mortality, hospital stay, ventilator days, rates of VAP, or hospital cost. 65 A small retrospective study compared 11 TBI subjects with early tracheostomy (within 8 d) versus 17 subjects with late tracheostomy (after 8 d) and found a decrease in 28-d mortality, but no differences in ICU mortality, ICU-free days, or ventilator-free days. 66 The largest retrospective cohort study compared 1,577 TBI subjects with one other organ system injury who received early tracheostomy (within 7 d) versus 1,527 TBI subjects who received late tracheostomy (after 7 d) and reported decreased hospital and ICU stay; decreased rates of adverse pulmonary, cardiac, infectious, and neurologic events; and improved independence at outcome with early tracheostomy, but also found increased hospital mortality.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…49 A retrospective cohort study compared 27 TBI subjects who received early tracheostomy (Ͻ 7 d of intubation) versus 28 TBI subjects with late tracheostomy (Ͼ 7 d of intubation) and found that early tracheostomy was associated with decreased ICU stay, but had no effect on hospital mortality, hospital stay, ventilator days, rates of VAP, or hospital cost. 65 A small retrospective study compared 11 TBI subjects with early tracheostomy (within 8 d) versus 17 subjects with late tracheostomy (after 8 d) and found a decrease in 28-d mortality, but no differences in ICU mortality, ICU-free days, or ventilator-free days. 66 The largest retrospective cohort study compared 1,577 TBI subjects with one other organ system injury who received early tracheostomy (within 7 d) versus 1,527 TBI subjects who received late tracheostomy (after 7 d) and reported decreased hospital and ICU stay; decreased rates of adverse pulmonary, cardiac, infectious, and neurologic events; and improved independence at outcome with early tracheostomy, but also found increased hospital mortality.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…The first category applies to patients who require long-term mechanical ventilation because of chronic respiratory failure, who cannot maintain respiratory function unassisted, or who cannot be weaned from ventilatory support. Numerous studies [4][5][6][7][8][9] have been done to determine the optimal interval from orotracheal intubation to placement of a tracheostomy tube, but no definitive recommendations have been made because of varied results in different populations of patients and in patients with different comorbid conditions. The American College of Chest Physicians 10 recommends consideration of a tracheostomy for patients who require an endotracheal tube for more than 21 days.…”
Section: Indications For Tracheotomymentioning
confidence: 99%
“…On the contrary, if the patient cannot be intubated and also cannot be adequately oxygenated or ventilated with bag valve mask ventilation, the situation may be rapidly lethal [5][6][7]13,18,19,24) . As mentioned above, cricothyrotomy and tracheostomy are the methods of choice for patients in a critical condition and who have a difficult airway, and these procedures should therefore be performed swiftly and without any complication 1,21) . Tracheostomy can cause many complications 1,15) .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, cricothyrotomy and tracheostomy are the methods of choice for patients in a critical condition and who have a difficult airway, and these procedures should therefore be performed swiftly and without any complication 1,21) . Tracheostomy can cause many complications 1,15) . We believe that methodical knowledge of neck region anatomy is the most important aspect of conventional cricothyrotomy and tracheostomy, and also for the application of new methods such as wire-guided cricothyrotomy and the Griggs technique for Tracheostomy 1,4,15,16,18,21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation